Pelatihan Pengelolaan Organisasi Pesantren bagi Pengurus Pondok Pesantren Al Urwatul Wutsqo Jombang - Solechan, Solechan; Afif, Zahrotun Ni’mah; Sintasari, Beny; Ma`arif, Muhammad Anas; Aprilianto, Andika (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
This service is designed with the aim of providing training in managing Islamic boarding school organizations to the administrators of the Al Urwatul Wutsqo Jombang Islamic Boarding School. As an Islamic educational institution, Islamic boarding schools play a crucial role in shaping the character of students and providing holistic education. To ensure sustainability and sustainable development, effective and efficient management is needed. Through this training, it is hoped that administrators at the Al Urwatul Wutsqo Jombang Islamic Boarding School can develop their managerial skills, understand and implement best practices in managing Islamic boarding schools. Mastery of modern management concepts, strategic planning, human resource management and Islamic boarding school finances is the focus in improving organizational governance. In this way, it is hoped that Islamic boarding schools can provide the best service to students, achieve better educational and da'wah goals, and strengthen their organizational foundations to support long-term development. Overall, it is hoped that this training will make a positive contribution in advancing Islamic boarding schools as quality and competitive Islamic educational institutions.